Using global and differential ratings of perceived exertion to measure internal training load in university volleyball players - Roy, X.; Caya, O.; Charron, J.; Comtois, A. S.; Sercia, P. (Journal of Australian Strength and Conditioning, 2020)
The Session-RPE (sRPE) is a simple and validated method to quantify internal training loads (iTL) but it may lack sensitivity to account for the varying central and peripheral physical demands in both training and competition. Differential ratings of perceived exertion (dRPE) could therefore discriminate which central and peripheral mediators may have the most influence on iTL. The present study quantified and compared the daily iTL from fifteen Canadian university female volleyball players during the second half of the 2016-2017 Réseau du sport étudiant du Québec (RSEQ) volleyball season using both methods. The relationship between both variables was measured using Spearman`s correlation coefficient. Mean daily sRPE iTL was 566 ± 260 arbitrary units (AU) and dRPE were 679 ± 342 AU, 538 ± 305 and 505 ± 339 AU for the lower limbs (dRPE-L), upper limbs (dRPE-U) and breathlessness (dRPE-B), respectively. dRPE showed statistically significant correlations with global sRPE (rho = 0.578, 0.453 and 0.483 for dRPE-L, dRPE-U and dRPE-B, respectively; p < 0.01). Bland Altman analysis showed levels of agreement (LoA) between sRPE and dRPE-L, dRPE-U and dRPE-B to be 119 AU, 1 AU and -52 AU, respectively. Results from this study show that dRPE can isolate distinct perceptual/sensory demands that are specific to the demands of a sport. However, it cannot be concluded that dRPE are more appropriate than sRPE but rather complement the use of sRPE. Having athletes provide either a global or differential response following a training session could therefore be used by the sports coach to make informed decisions about individualized training and recovery strategies.